2017
DOI: 10.18517/ijaseit.7.1.1790
|View full text |Cite
|
Sign up to set email alerts
|

Accelerator-Based Human Activity Recognition Using Voting Technique with NBTree and MLP Classifiers

Abstract: In evolution and ubiquitous computing systems, accelerometer-based human activity recognition has huge potential in a large number of application domains. Accelerometer-based human activity recognition aims to identify physical activities performed by human using accelerometer; a sensor device attached to the body and returns an actual valued estimate of acceleration along the x, y-and z-axes from which the sensor location can be estimated. In this study, an accelerator-based activity recognition model using v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The experimental results validate the claim in [52]. The advantage of voting is that it is unlikely that all classifiers will make the same mistake, as long as every error is made by a minority of the classifiers, an optimal classification can be achieved [53].…”
Section: Effect Of Voting and Ablation Study Of Ensemblesupporting
confidence: 75%
“…The experimental results validate the claim in [52]. The advantage of voting is that it is unlikely that all classifiers will make the same mistake, as long as every error is made by a minority of the classifiers, an optimal classification can be achieved [53].…”
Section: Effect Of Voting and Ablation Study Of Ensemblesupporting
confidence: 75%
“…In the DT method, a set of features must be selected correctly to have high accuracy for recognition. This method uses a sliding window [ 83 ], which has an excellent computational performance. Some research work using other sensors in conjunction with inertial sensors uses conceptual information to improve diagnostic accuracy [ 76 ].…”
Section: Har Analysismentioning
confidence: 99%
“…In [19,20,21,22,23,24,25] researchers have implemented the time domain and frequency domain feature extraction as a combined approach. Other researchers in [26,27,28,29,30,31] have used feature extraction in the time domain only, whilst, in [32] researchers applied the frequency domain and time-frequency domain. The authors in [33] have chosen the time domain, frequency domain and time-frequency domain for feature extraction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Romero et al [24] have found that One vs. one (OVO), OVO-SVM gives the best overall classification accuracy rate as 96.4%; whilst, Anguita et al [25] managed to gain a little improvement and reported best overall accuracy rate as 96.5% for classification using One vs. all (OVA), OVA-SVM. Researchers in [26,27,28], have analyzed the same dataset for walking, jogging, walking downstairs, walking, upstairs, sitting, and standing activities. A study conducted by Sufyan et al [26] found that classification on voting Multilayer perceptron (MLP) and NBtree give the best accuracy rate for classification based on each activity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation